The Mediation Role of Positive Social Attitudes in The Relationship Between Peer Influence and Smoking Behavior in Adolescents - Edwin, Vebby Amellia; Harahap, Nurlelasari; Welly, Welly; Husna, Riyana; Darwel, Darwel; Arlinda, Sari (RRZ Scientific Publishing, 2026)
Smoking among adolescents remains a serious public health problem because most adult smokers start the habit during their school age, while tobacco use causes more than 8 million deaths annually worldwide. Peer influence is thought to be an important factor in the smoking initiation process; however, the mechanisms by which this influence operates are not fully understood yet. This study aimed to analyze the relationship between cigarette offers from friends and smoking behavior in adolescents and to examine the mediating role of positive social attitudes toward smoking. This study used a cross-sectional design with secondary data from the 2021 Global Youth Tobacco Survey (GYTS) in Indonesia. Analysis was conducted through bivariate and multivariate logistic regression, as well as mediation analysis, after adjusting for age and sex. The results showed that cigarette offers from friends were strongly associated with smoking behavior (OR=21.7 [15.5–30.4]; p<0.001). A more favorable social attitude toward smoking was also significantly associated with smoking behavior (OR=1.20 [1.01–1.41]; p=0.036) and partially mediated the relationship, as indicated by a decrease in the OR from 21.7 to 20.4 after the mediator was included. It was concluded that peer influence operates not only directly but also through the formation of permissive social attitudes toward smoking. Prevention programs targeting peer group social norms and strengthening smoking cessation skills are recommended, and longitudinal studies are recommended to determine the direction of the relationship more clearly.